The Ability to Promote Efflux via ABCA1 Determines the Capacity of Serum Specimens with Similar HDL-C to Remove Cholesterol from Macrophages - de la Llera-Moya, Margarita (2010)
OBJECTIVES: We measured efflux from macrophages to apoB–depleted serum from 263 specimens and found instances where serum having similar HDL-C differed in their efflux capacity. Thus we wanted to elucidate why efflux capacity could be independent of total HDL-C or apoA-I. METHODS AND RESULTS: To understand why sera with similar HDL-C or apoA-I could differ in total efflux capacity we assessed their ability to promote efflux via the pathways expressed in cAMP treated J774 macrophages. Briefly, macrophages were pre-incubated with Probucol to block ABCA1, BLT-1 to block SR-BI and both inhibitors to measure residual efflux. ABCG1 efflux was measured with transfected BHK-1 cells. We used apoB-depleted serum from specimens with similar HDL-C values at the 25(th) and 75(Th) percentile. Specimens in each group were classified as having high or low efflux based on total efflux being above or below the group average. We found that, independently of HDL-C, sera with higher efflux capacity had a significant increase in ABCA1 mediated efflux which was significantly correlated to the concentration of preβ-1 HDL. The same result was obtained when these sera were similarly analyzed based on similar apoA-I. CONCLUSION: Sera with similar HDL-C or apoA-I differ in their ability to promote macrophage efflux due to differences in the concentration of preβ-1 HDL.